Integrated Vehicle Accident Detection and Location System - Md. Syedul Amin; Mamun Bin Ibne Reaz; Salwa Sheikh Nasir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Many accident victim lives could have been saved if vehicle accident information could be intimated to an evergencey rescue center automatically. This paper proposes an accident detection and location system by determining the deceleration and data fusion from accelerometers and GPS. The bias, drift and noise errors of accelerometers and GPS outage limitation are overcome by integrating with Kalman filter. The test result shows the correct deceleration for accident detection and location. The proposed system will be able to overcome the limitations of GPS/IMU and save valuable human lives.